2023
DOI: 10.1002/alr.23246
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the timing of biologic and surgical therapy for patients with refractory chronic rhinosinusitis with nasal polyposis (CRSwNP)

Abstract: IntroductionChronic rhinosinusitis with nasal polyposis (CRSwNP) is often treated with endoscopic sinus surgery (ESS), however, patients may require revision surgery due to recurrence. To date, no studies have compared outcomes for combined surgery and biologic therapy for CRSwNP compared to biologic therapy alone.MethodsRetrospective case‐control study of CRSwNP patients who underwent ESS while on dupilumab or mepolizumab (ESS‐biologic cohort), compared to CRSwNP patients on biologic therapy (biologic‐only co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The robustness of these results was corroborated by Phase III trials and the sub-analyses of these studies, which revealed a significant increase in olfactory function after 24-weeks, although with a difference of 10.5 points between groups, regardless of confounding factors such as disease duration, previous surgeries, and concomitant respiratory conditions. 109 , 149 The baseline olfactory scores correlated with all measured local and systemic type 2 inflammatory markers, except for total serum immunoglobulin E. Real-life studies also reinforce the positive impact of dupilumab on olfaction. Significant improvement in olfactory function, even in patients with persistent polyps, was observed in a cohort of 53 patients using dupilumab.…”
Section: Biologicals For Secondary Crsmentioning
confidence: 64%
See 1 more Smart Citation
“…The robustness of these results was corroborated by Phase III trials and the sub-analyses of these studies, which revealed a significant increase in olfactory function after 24-weeks, although with a difference of 10.5 points between groups, regardless of confounding factors such as disease duration, previous surgeries, and concomitant respiratory conditions. 109 , 149 The baseline olfactory scores correlated with all measured local and systemic type 2 inflammatory markers, except for total serum immunoglobulin E. Real-life studies also reinforce the positive impact of dupilumab on olfaction. Significant improvement in olfactory function, even in patients with persistent polyps, was observed in a cohort of 53 patients using dupilumab.…”
Section: Biologicals For Secondary Crsmentioning
confidence: 64%
“…The evaluations will consist of objective measures and various patient-reported questionnaires, treatment patterns, concomitant medications, long-term safety, and progression of CRSwNP, including those with coexisting diseases. 109 …”
Section: Efficacy In Patients With Crswnp and Aerdmentioning
confidence: 99%